2018
DOI: 10.3390/genes9020064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NKG2D Genetic Variants on Response to Anti-TNF Agents in Patients with Rheumatoid Arthritis

Abstract: A natural killer group 2 member D (NKG2D) acts as a powerful activating and co-stimulatory receptor on immune effector cells including NK and T cells. Disruptions within the NKG2D signalling pathway may trigger an exacerbated immune response and promote autoimmune reactions. The objective of the study was to evaluate a plausible role of polymorphisms within the NKG2D gene as a predictor of how effective anti-tumor necrosis factor (TNF) therapy is in rheumatoid arthritis (RA) patients. A total of 280 RA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…The moderate response was defined as either ΔDAS28 > 1.2 and DAS28 at endpoint > 3.2 or 0.6 < ΔDAS28 ≤ 1.2 and DAS28 at endpoint ≤ 5.1. A lack of response was defined as ΔDAS28 ≤ 0.6 or 0.6 < ΔDAS28 ≤ 1.2 and DAS28 at endpoint > 5.1, as previously described (Iwaszko et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate response was defined as either ΔDAS28 > 1.2 and DAS28 at endpoint > 3.2 or 0.6 < ΔDAS28 ≤ 1.2 and DAS28 at endpoint ≤ 5.1. A lack of response was defined as ΔDAS28 ≤ 0.6 or 0.6 < ΔDAS28 ≤ 1.2 and DAS28 at endpoint > 5.1, as previously described (Iwaszko et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Biologic agents successfully suppress disease symptoms, as well as stop further bone damage and reduce disability (Geiler et al 2011 ). Our previous studies showed that some genetic features may influence disease susceptibility or anti-TNF therapy outcome in RA patients (Bogunia-Kubik et al 2015 ; Gębura et al 2017 ; Iwaszko et al 2018 ; Świerkot et al 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in both MICA and NKG2D have been associated with RA, suggesting MICA and NKG2D as RA susceptibility genes ( 55 , 56 ). Moreover, a recent study evaluated the role of polymorphisms in KLRK1 gene with efficacy of α-TNF therapy in RA patients ( 57 ), identifying two polymorphisms associated with better response and two polymorphisms associated with inefficient response to therapy. More functional studies that would dissect the direct effect of the polymorphisms to the TNF production and resistance to α-TNF therapy would be beneficial to understand the impact of this association.…”
Section: Rheumatoid Arthritis (Ra) and Models Of Joint Inflammationmentioning
confidence: 99%
“…This Special Issue on DNA Variations in Evolution and Human Diseases features a series of studies that identify new pathological and protective DNA variations in common human diseases and conditions including chronic periodontitis [11], familial adenomatous polyposis [12], asthma [13], rheumatoid arthritis [14], multiple myeloma [15], dental implant failure [16], tooth agenesis [17], tuberculosis [18], and developmental disorders [19,20].…”
mentioning
confidence: 99%